Cardiomyopathies with left ventricular hypertrophy phenotype: prevalence of cardiac amyloidosis and clinical characteristics of patients - Kozliuk, A.S. (Medicni Perspektivi, 2025)
Cardiac amyloidosis was long considered a rare disease, primarily affecting the elderly. However, recent studies have demonstrated a higher prevalence, highlighting the need for further investigation, particularly in Ukraine, where data remain limited. The underdiagnosis of cardiac amyloidosis is primarily due to the low specificity of its clinical manifestations, which can mimic other cardiovascular diseases, particularly those presenting with a left ventricular hypertrophy phenotype. The aim of this study was to evaluate the prevalence and clinical characteristics of patients with cardiac amyloidosis among cardiomyopathies with the left ventricular hypertrophy phenotype, based on single-center data. This study was a retrospective analysis of medical records from the outpatient and inpatient departments of the SI “NSC “Strazhesko National Scientific Center of Cardiology and Regenerative Medicine of the NAMS of Ukraine” between 2020 and 2023. Data on subjective complaints, medical history, clinical examination findings, six-minute walk test results, and screening laboratory and instrumental evaluations were analyzed. Statistical analysis included confidence interval estimation, Pearson’s χ² test, one-way analysis of variance (ANOVA), and Tukey’s post hoc test. Data from 294 patients with left ventricular hypertrophy phenotypes were examined, including 177 cases (60.2%) of non-obstructive hypertrophic cardiomyopathy, 70 cases (23.8%) of hypertrophic cardiomyopathy with left ventricular outflow tract obstruction, and 47 cases (16%) of cardiac amyloidosis. The true prevalence of cardiac amyloidosis among cardiomyopathies with a left ventricular hypertrophy phenotype was estimated at 16% (CI 95%: 7.44-24.56%). Patients with cardiac amyloidosis were characterized by older age (56.8±11.7 years, F=6.85, p≤0.01), presence of congestive heart failure in the medical history (45 cases, χ2=65.54, p≤0.001), reduced distance covered in the 6-minute walk test (248.3±131.6 meters, F=10.77, p<0.001), signs of congestion in the systemic circulation (89%, 42 cases, χ2=64.56, p<0.001), and decreased left ventricular ejection fraction (54.5±15.1%, F=11.71, p≤0.05) compared to both groups of hypertrophic cardiomyopathy. Extracardiac manifestations of cardiac amyloidosis included proteinuria (83%, 39 cases), neuropathy (59.6%, 28 cases), hepatomegaly (55.3%, 26 cases), skin involvement and bruising (34%, 16 cases), carpal tunnel syndrome (23.4%, 11 cases), macroglossia (19.1%, 9 cases), digestive disturbances (12.8%, 6 cases), weight loss (19.1%, 9 cases), and thrombotic events at various sites (14.9%, 7 cases). Thus, cardiac amyloidosis is an underrecognized pathology, accounting for 16% of cardiomyopathies with a left ventricular hypertrophy phenotype. Compared to non-obstructive and obstructive hypertrophic cardiomyopathy, these patients are characterized by older age, more severe systemic conditions, decreased left ventricular systolic function, and systemic extracardiac manifestations. Multicenter studies are required to determine the true prevalence of cardiac amyloidosis in Ukraine.